Aesthetic norms and motivations of Subaltern Video-Filmmaking: comic skits and mobile journalism of the everyday in Zimbabwe - Ureke, Oswelled (Palgrave Macmillan, Cham., 2022)
Comic outfits Magamba Network, Bustop TV and P.O Box have gained popularity for their creative forms of youth activism in which they produce and disseminate, via social media, skits about ‘everyday’ issues in Zimbabwe. The chapter examines skits produced by the outfits, raising critical questions about external interference by professionalised, institutionalised and politicised commissioning agencies that paradoxically amplify and trivialise the subaltern’s representational agency. Methodologically, data is collected through archival collection of selected skits and interviews with the art activists (artivists). The data is subjected to thematic analysis. The chapter argues that external funding for the activities of these outfits creates a conundrum in that while it offers an assured means of sustainability, it also curtails creativity.